Influence of Barriers to Environmental Sustainability on Environmental Management Accounting in the Food and Beverage Manufacturing Firms - Smangele NZAMA; Odunayo Magret OLAREWAJU; Omolola A ARISE (Indonesia Strategic Sustainability, 2023)
Most companies make extensive use of environmental sustainability as they receive pressure to operate in an environmentally sustainable manner. Companies are struggling to implement environmental management accounting practices in their operations. Accordingly, research on environmental sustainability difficulties in the context of environmental management accounting in food and beverage manufacturing enterprises is limited. The paper investigates how the barriers to environmental sustainability influence the implementation of environmental management accounting (EMA) in the food and beverage manufacturing firms in Durban, South Africa. A quantitative research approach was applied, using convenience sampling because the data was collected during the strict regulations of the Covid-19 period. The Likert questionnaire (five-point scale) collected quantitative data and it was analyzed using SPSS, performing Pearson's correlation research and regression analysis. The Pearson's correlation coefficient findings show a statistically significant association between environmental sustainability bottlenecks and environmental management accounting in food and beverage manufacturing enterprises at (r = .250, p < 0.0005). As barriers to sustainability decrease, the implementation of environmental management accounting practices will be easier for these firms. The results of regression analysis, show the independent variable, barriers to sustainability, as a major predictor of environmental management accounting, B= 0.442, p< 0.05. It can be suggested that the SA government make the use of EMA practices mandatory for companies that have a negative impact on the environment.